Increased in vitro antimicrobial resistance of Mycoplasma pneumoniae isolates obtained from children in Beijing, China, in 2023 - Jia, Xinyu; Chen, Yujie; Gao, Yagang; Ren, Xue; Du, Bing; Zhao, Hanqing; Feng, Yanling; Xue, Guanhua; Cui, Jinghua; Gan, Lin; Feng, Junxia; Fan, Zheng; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionMycoplasma pneumoniae (M. pneumoniae), a common pathogen of community-acquired pneumonia in school-age children and adolescents, can cause epidemics worldwide. In late 2023, the incidence of M. pneumoniae infection among children reached a high level.MethodsWe investigated the in vitro antimicrobial susceptibility of 62 M. pneumoniae isolates obtained from children with pneumonia in Beijing between 2021 and 2023, and analyzed the correlation of antimicrobial susceptibility with molecular characteristics of isolates and clinical manifestations of patients.ResultsThe resistance rates of M. pneumoniae isolates against erythromycin and azithromycin were both 100% (62/62). The minimum inhibitory concentration (MIC) of acetylspiramycin (16-membered macrolides) was lower than that of erythromycin and azithromycin. The MIC of azithromycin in 2023 was notably higher compared to 2021 and 2022. No resistance to tetracycline and levofloxacin was observed. Genotypes P1 type 1 and P1 type 2 were identified in 74.2% and 25.8% of isolates, and M4-5-7-2 (61.3%) and M3-5-6-2 (22.6%) were predominant multi-locus variable-number tandem-repeat analysis (MLVA) types. The A2063G mutation was present in all isolates (100%). Among the patients, 45/59 cases (76.3%) had severe M. pneumoniae pneumonia, and 14/59 cases (23.7%) presented co-infection. The duration of fever was 12 days (1-30 days) and the fever duration after initiation of macrolide antibiotics treatment was 8 days (1-22 days).DiscussionOur study showed that macrolide-resistant M. pneumoniae (MRMP) with high in vitro antimicrobial resistance level may be the causative factor of the M. pneumoniae epidemic in late 2023 in Beijing, China. It is urgent to pay more attention to MRMP and the antibiotics choose.